2013
DOI: 10.1155/2013/206525
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Combined Aquaporin 3 and Aquaporin 5 Overexpression in Hepatocellular Carcinoma

Abstract: Background. Aquaporin (AQP) 3 and AQP 5 are involved in tumorigenesis and tumor progression of several tumor types. Aim. To investigate expression patterns and clinical significance of AQP3 and AQP5 in hepatocellular carcinoma (HCC). Methods. Immunohistochemistry was performed to detect the expression of AQP3 and AQP5 in HCC tissues. Results. Immunohistochemistry analysis showed the increased expression of AQP3 and AQP5 protein levels in HCC tissues compared with their adjacent nonneoplastic tissues (both P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 25 publications
4
52
0
Order By: Relevance
“…Increasing evidence shows that a correlation exists between AQP3 expression and cancer progression and prognosis, particularly in distant or lymphatic metastasis of colorectal, esophageal, hepatocellular, and gastric malignant cancers (11)(12)(13)(14). In the current study, we showed that overexpressing AQP3 promoted the migration of breast cancer cells toward CXCL12 in association with higher intracellular H 2 O 2 levels and enhanced susceptibility to Akt activation in vitro.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Increasing evidence shows that a correlation exists between AQP3 expression and cancer progression and prognosis, particularly in distant or lymphatic metastasis of colorectal, esophageal, hepatocellular, and gastric malignant cancers (11)(12)(13)(14). In the current study, we showed that overexpressing AQP3 promoted the migration of breast cancer cells toward CXCL12 in association with higher intracellular H 2 O 2 levels and enhanced susceptibility to Akt activation in vitro.…”
Section: Discussionsupporting
confidence: 60%
“…AQP3 is expressed in various cancer cells derived from diverse types of cancer tissues, including breast, colon, and lung (9, 10). Recent results from clinical studies have suggested the relevance of AQP3 expression in tumor progression and the prognosis of several malignant cancers (11)(12)(13)(14). In vitro studies using cancer cell lines have implicated AQP3 expression in cancer cell proliferation and migration (15-17).…”
mentioning
confidence: 99%
“…A selective defect in lacrimal gland AQP5 trafficking is responsible for Sjögren’s syndrome characterized by dry eye and mouth (Tsubota, Hirai, King, Agre, & Ishida, 2001). Elevated AQP5 expression is associated with advanced tumor stage, positive distant metastasis, and/or unfavorable prognosis in several types of cancer (Guo et al, 2013; Watanabe et al, 2009; Yang, Shi, Cheng, & Deng, 2006; Zhang et al, 2010). However, pathological expression of AQP5 in kidney had not been described until our recent report (Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…AQPs are strongly expressed by various tumor cells, especially those from aggressive tumors [2][3][4] . The involvement of AQPs in cell migration and proliferation suggests that AQPs could play key roles in tumor biology [5][6][7] . Consistently, AQP1-expressing tumor cells demonstrate enhanced metastatic potential and increased local infiltration [5,8,9] .…”
Section: Expression Of Aqp1 Was Associated With Apoptosis and Survivamentioning
confidence: 99%